Light and Shadows in Holography: a possible dialogue between Art and Science by using artistic holography - Oliveira, Rosa Maria (2012)
The use of new technologies in visual arts brings a new way of understanding shape relationships, a new form of perceiving and appreciating the configurations that present them to our perceptive organization. Light has been seen as a plastic material since Moholy-Nagy created and presented his work of art “Light-Space-Modulator”. When Dennis Gabor discovered Holography new approaches of the use of Light as an Art medium became possible. The basic holographic interactivity inherent to this technology can be amplified and diversified by the presentation in installations that use a pre-established system of controlling the light, or reacting to the observer’s presence and movements. The holographic installation adds or emphasises other factors like time to the holographic images. The global work of art can only be perceived by an interactive relationship between the observer and the work. Nowadays several artists use Artistic Holography as their preferential medium. This paper is a presentation of the research of the author in this field and also a tribute to these two men, an artist and a scientist that contributed to the development of a better dialogue between Art and Science in ways that were impossible before their works. A Hologram is light; but is there light without shadows?